Multiple regulatory elements in the interleukin-6 gene mediate induction by prostaglandins, cyclic AMP, and lipopolysaccharide. - Dendorfer, U (1994)
Induction of interleukin-6 (IL-6) gene expression is mediated by numerous agents involving all major signal transduction pathways. We have compared the effects of prostaglandins and their second messenger cyclic AMP (cAMP) with the effect of lipopolysaccharide (LPS) on IL-6 gene expression. We demonstrate that secretion of IL-6 is induced by cAMP in murine monocytic PU5-1.8 cells, even though to a lesser extent than by LPS. Nevertheless, cAMP and prostaglandins of the E series in the presence of theophylline induce transcription of the IL-6 promoter more strongly than LPS, suggesting distinctive effects of cAMP and LPS on posttranscriptional events. Mutations within four regulatory elements, namely, the multiple response element (MRE), AP-1, NF-IL6, and NF-kappa B sites, significantly reduce, but do not completely abrogate, inducibility by cAMP and prostaglandin E1, whereas alterations of four additional sites have no effects. LPS-induced promoter activity, however, is almost completely abolished by mutations in the NF-kappa B site, suggesting that a single regulatory element is crucial for inducibility by LPS. Stimulation by cAMP is correlated with the binding of inducible factors to the AP-1, NF-IL6, and NF-kappa B elements, whereas factors binding to the MRE are constitutively expressed. Recombinant cAMP response element-binding protein binds to the MRE, indicating a potential role for this factor in the cAMP response. Our results suggest that cAMP and prostaglandins act through multiple, partially redundant regulatory elements to induce IL-6 expression in monocytic cells. Nuclear events that overlap partially with the LPS response but also exhibit distinctive features are involved.